Short-term follow-up study of rotating stable prosthesis and simple hinge prosthesis in the treatment of malignant bone tumors of proximal tibia - Zi-Meng CHEN; Huo-Wen LIU; Min-Hao WU; Jun LEI; Lin CAI (Yixue xinzhi zazhi)
Objective To explore the difference between rotationally stable prosthesis and hinge prosthesis in the treatment of malignant bone tumors in proximal tibia, and to provide reference for practical use.Methods Clinical data of 60 patients with proximal tibial bone malignancy treated with two different types of prosthesis in our hospital from June 2015 to June 2019 were retrospectively analyzed and divided into control group and study group. Thirty patients received simple hinge prosthesis replacement as the control group and 30 patients received Rotating stable prosthesis replacement as the research group.Results Before treatment, there was no significant difference in knee joint function score between the two groups (P > 0.05); after treatment, the score of study group was (23.27±2.12) and control group was (19.13±4.52), which were significantly higher than before, with t values were 10.811 and 3.713, respectively (P < 0.05); and after treatment, the score of study group was significantly higher than control group, t values was 4.542(P < 0.05). The scores of social activities, physical activities, emotions, pain, sleep and energy in the study group were (27.25±3.16), (41.17±2.59), (20.18±2.13), (30.26±4.15), (25.18±2.19), (33.25±3.47), respectively, lower than control group, with t values of 4.609, 13.565, 7.724, 6.629, 19.632 and 5.539, respectively (P < 0.05). In study group, there were only 3 cases with tumors recurrence and 1 case with intra-articular hemorrhage, the incidence rate was 13.33%, which was significantly lower than 40% in control group, and χ2 was 4.176, the difference was statistically significant (P < 0.05).Conclusion Rotary stable prosthesis can effectively improve the recovery of knee joint function, the quality of life and reduce complications, which is worthy of clinical application. However, it is worth noting that due to the possibility of recurrence, indications should be strictly observed in the selection of limb salvage surgery.